Antibacterial plastic and preparation method thereof
By combining cuprous oxide/antimony trioxide nanocomposite with ZIF-8 carrier, composite antibacterial agents are prepared and added to polycarbonate resin with other additives, the existing antibacterial plastic antibacterial agents are solved by uneven dispersion and thermal stability of existing antibacterial plastic antibacterial agents. The problem of poor performance and poor antibacterial effect is obtained, and antibacterial plastics with high antibacterial properties, flame retardant and toughness are obtained.
Patent Information
- Application Number
- CN202411691523.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
AI Technical Summary
The existing polycarbonate-based antibacterial plastics have problems such as uneven dispersion of antibacterial agents, poor thermal stability and poor antibacterial effect.
Copper oxide/antimony trioxide nanocomposite is used to combine with ZIF-8 carrier to prepare composite antibacterial agents, and add them to polycarbonate resins with light diffusants, light stabilizers, antioxidants and other additives, and manufacture them by extrusion. Antibacterial plastics are prepared by particle method.
The obtained antibacterial plastics have extremely high antibacterial properties against E. coli and Staphylococcus aureus, while maintaining high flame retardant performance, good toughness and apparent performance, solving the problem of flame retardant performance and toughness reduction after the addition of antibacterial agents.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, and in particular to an antibacterial plastic and a preparation method thereof. Background Art
[0002] With the improvement of living standards, people pay more and more attention to health. In order to avoid the reproduction of bacteria in plastic parts and improve the safety of products, the requirements for plastics to inhibit bacterial reproduction are becoming increasingly stringent, especially antibacterial plastics, which are widely used in many aspects such as medical devices, food packaging, kitchen supplies, and auto parts. Antibacterial plastics mainly add a small amount of antibacterial agent to the plastic substrate, so that the plastic products themselves have antibacterial properties, which can kill bacteria on the surface of the products or inhibit bacterial growth and reproduction within a certain period of time. Antibacterial materials are mainly divided into three categories according to the source of antibacterial agents, namely natural antibacterial materials, organic antibacterial materials and inorganic antibacterial materials. Compared with the other two antibacterial materials, inorganic antibacterial materials have better durability, higher stability and lower toxicity, especially they will not cause bacterial resistance. Therefore, in order to meet market demand, inorganic antibacterial materials have aroused widespread interest and become one of the research hotspots.
[0003] Polycarbonate (PC) is a general term for a class of polymers containing carbonate groups in the molecular chain. The alternating combination of flexible carbonate bonds and rigid aryl alkyl groups in the PC macromolecular chain makes it have the advantages of light weight, impact resistance, good transparency, good dielectric properties, heat resistance, cold resistance, etc., and is widely used in optical materials, plastic packaging, and medical devices. Because PC is easily contaminated by microorganisms during use, giving PC good antibacterial properties can effectively broaden the application range of PC. At present, antibacterial agents that improve the antibacterial properties of polymers mainly include quaternary phosphonium salts, Ag nanoparticles, and ZnO nanoparticles. Among them, Ag and ZnO nanoparticles in inorganic antibacterial agents are cytotoxic and difficult to disperse in polymers. Although organic antibacterial agents such as quaternary ammonium salts and quaternary phosphonium salts have excellent antibacterial properties and durability, they have poor thermal stability and are prone to thermal decomposition during polymer processing. Therefore, existing polycarbonate-based antibacterial plastics have defects such as uneven dispersion of antibacterial agents, poor thermal stability, and poor antibacterial effects, which makes the use of this technology very limited. Summary of the invention
[0004] The purpose of the present invention is to provide an antibacterial plastic and a preparation method thereof to solve the following technical problems: Existing polycarbonate-based antibacterial plastics have problems such as uneven dispersion of antibacterial agents, poor thermal stability and poor antibacterial effect.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antibacterial plastic comprises at least the following components in parts by weight: Polycarbonate resin 70-90 parts; 10-30 parts of composite antibacterial agent; 1-2 parts of light diffuser; Light stabilizer 0.1-1 part; Antioxidant 0.1-1 part; 1-5 parts of additives; Wherein, the composite antibacterial agent is at least a composite antibacterial agent comprising cuprous oxide / ZIF-8.
[0006] As a further solution of the present invention: the composite antibacterial agent also includes antimony trioxide.
[0007] As a further solution of the present invention: the preparation method of the composite antibacterial agent comprises at least the following steps: Dissolve zinc acetate hexahydrate and 2-methylimidazole in methanol solution respectively, mix until transparent, react at 40-60°C for 4-6h, centrifuge and wash after the reaction, and dry to obtain ZIF-8 carrier; Adding sodium hydroxide aqueous solution to copper acetate aqueous solution, heating and stirring in a constant temperature water bath at 70-90°C for 30-40 minutes, then adding ascorbic acid aqueous solution, continuing to heat and stir in a constant temperature water bath at 70-90°C for 50-60 minutes, after the reaction is completed, adding ethylene glycol antimony ethanol solution, stirring at constant temperature for 10-20 minutes, finally, adjusting the pH of the solution to 8-9 by dropping phosphoric acid, then transferring the mixed solution into a reactor, heating at 110-120°C for 10-12 hours, cooling the reactor to room temperature after hydrothermal treatment, taking out the solution, centrifuging and washing, and drying at 50-60°C to obtain a cuprous oxide / antimony trioxide nanocomposite material; The ZIF-8 carrier and the cuprous oxide / antimony trioxide nanocomposite material are placed in a methanol solution and stirred for 24-36 hours, washed by centrifugation, and dried at 50-60° C. to obtain a composite antibacterial agent.
[0008] As a further embodiment of the present invention: the molar ratio of the zinc acetate hexahydrate to the 2-methylimidazole is 1:1-3.
[0009] As a further embodiment of the present invention: the mass ratio of the copper acetate, the sodium hydroxide and the ascorbic acid is 1:1-1.6:0.2-0.5, the mass ratio of the copper acetate and the ethylene glycol antimony is 1:1-10, and the mass ratio of the cuprous oxide / antimony trioxide nanocomposite material and the ZIF-8 carrier is 1:1-10.
[0010] As a further embodiment of the present invention: the light stabilizer is at least one of benzylmalonate, 2-thiazolyl-3-pyridyl acrylonitrile, dibutyltin bis(monobutyl maleate), o-hydroxybenzophenone, benzotriazole or salicylate.
[0011] As a further embodiment of the present invention: the light diffuser is at least one of polyisobutyl methacrylate, polystyrene particles, polysiloxane particles, acrylic resin, silicon dioxide, barium sulfate or organic silicon light diffuser JCP-592.
[0012] As a further embodiment of the present invention: the antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant 1076 or antioxidant 626.
[0013] As a further solution of the present invention: the additive includes at least one of a toughening agent, a lubricant or a dispersant.
[0014] A method for preparing the antibacterial plastic as described in any one of the above, comprising at least the following preparation steps: Add the composite antibacterial agent, antioxidant and light diffuser into a high-speed mixer and blend for 3-5 minutes; Then add the light stabilizer, additives and polycarbonate resin and continue blending for 5-10 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.
[0015] Beneficial effects of the present invention: In the present application, a composite antibacterial agent is prepared by carrying a cuprous oxide / antimony trioxide nanocomposite on a ZIF-8 carrier, and then added to a polycarbonate resin with a light diffuser, a light stabilizer, an antioxidant and other additives to prepare an antibacterial plastic. The obtained antibacterial plastic has extremely high antibacterial properties against Escherichia coli and Staphylococcus aureus. The preparation method of the present application can ensure that the material has high flame retardant properties, good toughness and surface properties while adding an inorganic antibacterial agent, solve the problem of decreased flame retardant properties and toughness after adding an antibacterial agent to the material, and can be widely used in the fields of optical materials, plastic packaging and medical devices. In the present application, the preparation method of the antibacterial plastic is to first mix the composite antibacterial agent with an antioxidant and a light diffuser, so that the antioxidant and the light diffuser are wrapped, and then the composite antibacterial agent is mixed with a light stabilizer, an additive and a polycarbonate resin, and then extruded, cooled, pulled and granulated to obtain the antibacterial plastic. The preparation method of the present application improves the dispersibility of the antibacterial agent, and can utilize the covering effect of the light diffuser and the antioxidant effect of the antioxidant to solve the problem of nano-scale cuprous oxide failure due to high-temperature oxidation above 200°C, meet the use temperature of extrusion granulation and injection molding, and avoid the failure of the antibacterial performance of cuprous oxide and the problem of too dark color of polycarbonate resin.
[0016] The ZIF-8 synthesized in this application is a dodecahedral crystal with a microporous structure. The ZIF-8 material can release Zn in the solution. 2+ , low toxicity Zn 2+ It interacts with anions on the surface of bacterial cell membranes and binds tightly. 2+ After entering the bacteria, it combines with the protein thiol groups in the body, causing the inactivation of protein and cell synthase functions, and the bacteria lose the ability to grow and reproduce, and then release metal cations to perform continuous and repeated sterilization. The cuprous oxide / antimony trioxide nanocomposite is loaded on ZIF-8, so that more cuprous oxide / antimony trioxide nanocomposite is evenly dispersed on the outer surface of ZIF-8, increasing the contact area between the antibacterial material and the bacteria, thereby better exerting the antibacterial effect of the cuprous oxide / antimony trioxide nanocomposite. In addition, the adsorption of cuprous oxide / antimony trioxide nanocomposite on the surface of ZIF-8 can make Zn 2+ Slow release not only achieves synergistic antibacterial effect, but also prolongs the duration of antibacterial effect.
[0017] In the present application, the cuprous oxide / antimony trioxide nanocomposite material is prepared by a hydrothermal method using cupric acetate as the copper source, ethylene glycol antimony as the antimony source, and ascorbic acid as the reducing agent, and meets the requirements of antibacterial and flame retardant at the same time. Compared with cuprous oxide or antimony trioxide alone, the antibacterial performance against Escherichia coli and Staphylococcus aureus is significantly improved, and the antibacterial rates of the composite material against Escherichia coli and Staphylococcus aureus are both >99%, showing excellent antibacterial performance. Using the principle of electrostatic adsorption, cuprous oxide is loaded onto the surface of antimony trioxide, and copper atoms partially replace antimony atoms, and Cu-O-Sb bonding bonds are formed by electron transfer to prepare a cuprous oxide / antimony oxide nanocomposite material. The antibacterial performance is significantly improved by the synergistic effect of cuprous oxide and antimony trioxide. Due to the coupling of cuprous oxide, under the irradiation of visible light, the e bonding between cuprous oxide and antimony trioxide is 1.5 times that between cuprous oxide and antimony trioxide. - and h + The transfer of copper oxide promotes the separation of charge carriers and produces more active species. These active substances will damage the cell membrane, leak the cell contents, oxidize proteins, and further lead to bacterial death, thus improving the antibacterial properties of cuprous oxide or antimony trioxide alone. DETAILED DESCRIPTION
[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1 The preparation method of the composite antibacterial agent comprises the following steps: Zinc acetate hexahydrate and 2-methylimidazole in a molar ratio of 1:2 were mixed in a methanol solution in a volume ratio of 1:2 until transparent, and then mixed and reacted at a temperature of 50°C for 6 hours. After the reaction, centrifuged at a speed of 8000 rpm for 10 minutes and washed with methanol. The above steps were repeated at least three times, and then dried to obtain a ZIF-8 carrier; Dissolve copper acetate, sodium hydroxide and ascorbic acid in deionized water to obtain copper acetate aqueous solution, sodium hydroxide aqueous solution and ascorbic acid aqueous solution, dissolve ethylene glycol antimony in anhydrous ethanol, and ultrasonically disperse for 30 minutes to obtain ethylene glycol antimony ethanol solution, and the mass ratio of copper acetate, sodium hydroxide, ascorbic acid and ethylene glycol antimony is 1:1.5:0.3:4, then add sodium hydroxide aqueous solution to copper acetate aqueous solution, heat and stir in a constant temperature water bath at 80°C for 30 minutes, then add ascorbic acid aqueous solution, continue to heat and stir in a constant temperature water bath at 80°C for 60 minutes, after the reaction is completed, add ethylene glycol antimony ethanol solution, and stir at constant temperature for 20 minutes, finally, adjust the pH of the solution to 8-9 by dropping phosphoric acid, then transfer the mixed solution into a reactor, heat at 120°C for 12 hours, after hydrothermal reaction, cool the reactor to room temperature, take out the solution, centrifuge and wash, and dry at 60°C to obtain cuprous oxide / antimony trioxide nanocomposite material; The cuprous oxide / antimony trioxide nanocomposite material and the ZIF-8 carrier were added to a methanol solution at a mass ratio of 1:8, stirred for 24 hours, centrifuged and washed, and dried at 60° C. to obtain a composite antibacterial agent.
[0020] Example 2 The preparation method of the composite antibacterial agent comprises the following steps: Zinc acetate hexahydrate and 2-methylimidazole in a molar ratio of 1:3 were mixed in a methanol solution in a volume ratio of 1:3 until transparent, and then mixed and reacted at a temperature of 50°C for 6 hours. After the reaction, centrifuged at a speed of 8000 rpm for 10 minutes and washed with methanol. The above steps were repeated at least three times, and then dried to obtain a ZIF-8 carrier; Dissolve copper acetate, sodium hydroxide and ascorbic acid in deionized water to obtain copper acetate aqueous solution, sodium hydroxide aqueous solution and ascorbic acid aqueous solution, dissolve ethylene glycol antimony in anhydrous ethanol, and ultrasonically disperse for 30 minutes to obtain ethylene glycol antimony ethanol solution, and the mass ratio of copper acetate, sodium hydroxide, ascorbic acid and ethylene glycol antimony is 1:1.5:0.5:5, then add sodium hydroxide aqueous solution to copper acetate aqueous solution, heat and stir in a constant temperature water bath at 80°C for 30 minutes, then add ascorbic acid aqueous solution, continue to heat and stir in a constant temperature water bath at 80°C for 60 minutes, after the reaction is completed, add ethylene glycol antimony ethanol solution, and stir at constant temperature for 20 minutes, finally, adjust the pH of the solution to 8-9 by dropping phosphoric acid, then transfer the mixed solution into a reactor, heat at 120°C for 12 hours, after hydrothermal reaction, cool the reactor to room temperature, take out the solution, centrifuge and wash, and dry at 60°C to obtain cuprous oxide / antimony trioxide nanocomposite material; The cuprous oxide / antimony trioxide nanocomposite material and the ZIF-8 carrier were added into a methanol solution at a mass ratio of 1:10, stirred for 24 hours, centrifuged and washed, and dried at 60° C. to obtain a composite antibacterial agent.
[0021] Example 3 The preparation method of antibacterial plastic comprises the following steps: 20 parts by weight of the composite antibacterial agent prepared in Example 1, 0.4 parts by weight of antioxidant 1010 and 1.3 parts by weight of light diffusing agent nano-silicon dioxide were added to a high-speed mixer and blended for 4 minutes; Then, 0.3 parts by weight of a light stabilizer, o-hydroxybenzophenone, 3 parts by weight of an additive and 75 parts by weight of a polycarbonate resin were added and blended for 8 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.
[0022] Example 4 The preparation method of antibacterial plastic comprises the following steps: 20 parts by weight of the composite antibacterial agent prepared in Example 2, 0.4 parts by weight of antioxidant 1010 and 1.3 parts by weight of light diffusing agent nano-silicon dioxide were added to a high-speed mixer and blended for 4 minutes; Then, 0.3 parts by weight of a light stabilizer, o-hydroxybenzophenone, 3 parts by weight of an additive and 75 parts by weight of a polycarbonate resin were added and blended for 8 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.
[0023] Example 5 The preparation method of antibacterial plastic comprises the following steps: 15 parts by weight of the composite antibacterial agent prepared in Example 1, 0.5 parts by weight of antioxidant 1010, and 1 part by weight of light diffusing agent polysiloxane particles were added to a high-speed mixer and blended for 4 minutes; Then, 0.5 parts by weight of a light stabilizer dibutyltin bis(monobutyl maleate), 3 parts by weight of an additive and 80 parts by weight of a polycarbonate resin were added and blended for 8 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.
[0024] Example 6 The preparation method of antibacterial plastic comprises the following steps: 15 parts by weight of the composite antibacterial agent prepared in Example 2, 0.5 parts by weight of antioxidant 1010 and 1 part by weight of light diffusing agent polysiloxane particles were added to a high-speed mixer and blended for 4 minutes; Then, 0.5 parts by weight of a light stabilizer dibutyltin bis(monobutyl maleate), 3 parts by weight of an additive and 80 parts by weight of a polycarbonate resin were added and blended for 8 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.
[0025] Comparative Example 1 The preparation method of the antibacterial agent comprises the following steps: The preparation of ZIF-8 support was omitted; A cuprous oxide / antimony trioxide nanocomposite material was prepared as an antibacterial agent, and the preparation components and method were the same as those in Example 1.
[0026] The preparation method of the antibacterial plastic comprises the following steps: The antibacterial agent prepared in this comparative example was replaced with the composite antibacterial agent prepared in Example 1 in equal amount, and the other components and preparation method were the same as in Example 1 to obtain an antibacterial plastic.
[0027] Comparative Example 2 The preparation method of the antibacterial agent comprises the following steps: The components and preparation method of the ZIF-8 carrier are the same as those in Example 1; Dissolve copper acetate, sodium hydroxide and ascorbic acid in deionized water to obtain copper acetate aqueous solution, sodium hydroxide aqueous solution and ascorbic acid aqueous solution, dissolve ethylene glycol antimony in anhydrous ethanol, and ultrasonically disperse for 30 minutes to obtain ethylene glycol antimony ethanol solution, and the mass ratio of copper acetate, sodium hydroxide and ascorbic acid is 1:1.5:0.3, then add sodium hydroxide aqueous solution to copper acetate aqueous solution, heat and stir in a constant temperature water bath at 80°C for 30 minutes, then add ascorbic acid aqueous solution, continue to heat and stir in a constant temperature water bath at 80°C for 60 minutes, after the reaction is completed, adjust the pH of the solution to 8-9 by dropping phosphoric acid, wash by centrifugation, and dry at 60°C to obtain cuprous oxide nanomaterials; The cuprous oxide nanocomposite material and the ZIF-8 carrier were added to a methanol solution at a mass ratio of 1:4, stirred for 24 hours, centrifuged and washed, and dried at 60° C. to obtain an antibacterial agent.
[0028] The preparation method of the antibacterial plastic comprises the following steps: The antibacterial agent prepared in this comparative example was replaced with the composite antibacterial agent prepared in Example 1 in equal amount, and the other components and preparation method were the same as in Example 1 to obtain an antibacterial plastic.
[0029] Comparative Example 3 The preparation method of the antibacterial agent comprises the following steps: The preparation of ZIF-8 support was omitted; Copper acetate, sodium hydroxide and ascorbic acid were respectively dissolved in deionized water to obtain copper acetate aqueous solution, sodium hydroxide aqueous solution and ascorbic acid aqueous solution, ethylene glycol antimony was dissolved in anhydrous ethanol, ultrasonically dispersed for 30 minutes, and ethylene glycol antimony ethanol solution was obtained, and the mass ratio of copper acetate, sodium hydroxide and ascorbic acid was 1:1.5:0.3, and then the sodium hydroxide aqueous solution was added to the copper acetate aqueous solution, heated and stirred in a constant temperature water bath at 80°C for 30 minutes, and then the ascorbic acid aqueous solution was added, and continued to heat and stir in a constant temperature water bath at 80°C for 60 minutes. After the reaction was completed, phosphoric acid was added dropwise to adjust the pH of the solution to 8-9, centrifuged and washed, and dried at 60°C to obtain cuprous oxide nanomaterials and antibacterial agents.
[0030] The preparation method of the antibacterial plastic comprises the following steps: The antibacterial agent prepared in this comparative example was replaced with the composite antibacterial agent prepared in Example 1 in equal amount, and the other components and preparation method were the same as in Example 1 to obtain an antibacterial plastic.
[0031] Comparative Example 4 The preparation method of the antibacterial plastic comprises the following steps: 75 parts by weight of polycarbonate resin, 20 parts by weight of the composite antibacterial agent prepared in Example 1, 0.4 parts by weight of antioxidant 1010, 0.3 parts by weight of light stabilizer o-hydroxybenzophenone, 3 parts by weight of additives and 1.3 parts by weight of light diffuser nano-silica were added to a high-speed mixer and blended for 10 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.
[0032] Performance Testing Antibacterial performance: tested in accordance with GB / T 31402-2015, the test bacteria were Escherichia coli AS 1.90 and Staphylococcus aureus ACTT 6538P; the test results are shown in the table below; Mechanical properties: Tested in accordance with GB / T 1040-2006, with a tensile rate of 5 mm / min; the test results are shown in the table below; Flame retardant performance: According to GB / T 2406-2009, the oxygen index value of antibacterial plastics was tested as an evaluation index of flame retardant performance; the test results are shown in the table below;
[0033] As can be seen from the above table, the antibacterial plastics prepared in Examples 3-6 of the present application have excellent antibacterial properties, and after adding the composite antibacterial agent, their flame retardant properties are also improved, and the mechanical properties are also reduced. The composite antibacterial agent prepared in Comparative Example 1 did not add ZIF-8, and the antibacterial property of the obtained plastic was reduced. The composite antibacterial agent prepared in Comparative Example 2 did not add antimony trioxide, and the flame retardant property of the obtained antibacterial plastic was greatly reduced, and the antibacterial property was also reduced. In Comparative Example 3, only cuprous oxide was prepared as an antibacterial agent, and the antibacterial property and flame retardant property of the obtained plastic were greatly reduced. In Comparative Example 4, all raw materials were directly mixed to prepare the antibacterial plastic, and the performance of the obtained antibacterial plastic in all aspects was reduced, indicating that the performance of the antibacterial plastic obtained by the preparation method of the present application is excellent in all aspects.
[0034] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. An antibacterial plastic, characterized in that: At least the following components by weight: Polycarbonate resin 70-90 parts; 10-30 parts of composite antibacterial agent; 1-2 parts of light diffuser; Light stabilizer 0.1-1 part; Antioxidant 0.1-1 part; 1-5 parts of additives; Wherein, the composite antibacterial agent is at least a composite antibacterial agent comprising cuprous oxide / ZIF-8.
2. The antibacterial plastic according to claim 1, characterized in that: The composite antibacterial agent also includes antimony trioxide.
3. The antibacterial plastic according to claim 1, characterized in that: The preparation method of the composite antibacterial agent comprises at least the following steps: Dissolve zinc acetate hexahydrate and 2-methylimidazole in methanol solution respectively, mix until transparent, react at 40-60°C for 4-6h, centrifuge and wash after the reaction, and dry to obtain ZIF-8 carrier; Adding sodium hydroxide aqueous solution to copper acetate aqueous solution, heating and stirring in a constant temperature water bath at 70-90°C for 30-40 minutes, then adding ascorbic acid aqueous solution, continuing to heat and stir in a constant temperature water bath at 70-90°C for 50-60 minutes, after the reaction is completed, adding ethylene glycol antimony ethanol solution, stirring at constant temperature for 10-20 minutes, finally, adjusting the pH of the solution to 8-9 by dropping phosphoric acid, then transferring the mixed solution into a reactor, heating at 110-120°C for 10-12 hours, cooling the reactor to room temperature after hydrothermal treatment, taking out the solution, centrifuging and washing, and drying at 50-60°C to obtain a cuprous oxide / antimony trioxide nanocomposite material; The ZIF-8 carrier and the cuprous oxide / antimony trioxide nanocomposite material are placed in a methanol solution and stirred for 24-36 hours, washed by centrifugation, and dried at 50-60° C. to obtain a composite antibacterial agent.
4. The antibacterial plastic according to claim 3, characterized in that: The molar ratio of the zinc acetate hexahydrate to the 2-methylimidazole is 1:1-3.
5. The antibacterial plastic according to claim 3, characterized in that: The mass ratio of the copper acetate, the sodium hydroxide and the ascorbic acid is 1:1-1.6:0.2-0.5, the mass ratio of the copper acetate and the antimony glycolate is 1:1-10, and the mass ratio of the cuprous oxide / antimony trioxide nanocomposite material and the ZIF-8 carrier is 1:1-10.
6. The antibacterial plastic according to claim 1, characterized in that: The light stabilizer is at least one of benzylmalonate, 2-thiazolyl-3-pyridyl acrylonitrile, dibutyltin bis(monobutyl maleate), o-hydroxybenzophenone, benzotriazole or salicylate.
7. The antibacterial plastic according to claim 1, characterized in that: The light diffuser is at least one of polyisobutyl methacrylate, polystyrene particles, polysiloxane particles, acrylic resin, silicon dioxide, barium sulfate or organic silicon light diffuser JCP-592.
8. The antibacterial plastic according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 168 , antioxidant 1076 or antioxidant 626 .
9. The antibacterial plastic according to claim 1, characterized in that: The additive includes at least one of a toughening agent, a lubricant or a dispersant.
10. A method for preparing the antibacterial plastic according to any one of claims 1 to 9, characterized in that: The method comprises at least the following preparation steps: Add the composite antibacterial agent, antioxidant and light diffuser into a high-speed mixer and blend for 3-5 minutes; Then add the light stabilizer, additives and polycarbonate resin and continue blending for 5-10 minutes to obtain a premix; The premix is added into a screw extruder, and extrusion granulation is performed at 240-260° C. The extruded melt strip is cooled, pulled, and granulated to obtain an antibacterial plastic.